Athens and Jerusalem god, humans, and nature - Novak, David 1941- (Toronto Buffalo London University of Toronto Press, 2019)
Philosophy and Theology -- God, Humans, and Nature -- Humans and Nature -- Philo and Plato -- Maimonides and Aristotle -- Kant's Challenge to Theology.
"What is the relation of philosophy and theology? This question has been a matter of perennial concern in the history of Western thought. Written by one of the premier philosophers in the areas of Jewish ethics and interfaith issues between Judaism and Christianity, Athens and Jerusalem contends that philosophy and theology are not mutually exclusive. Based on the Gifford Lectures David Novak delivered at the University of Aberdeen in 2017, this book explores the commonalities and common concerns that exist between philosophy and theology on metaphysical, epistemological, and ethical questions. Where are they different and where are they the same? And, how can they speak to one another?"--
Includes bibliographical references (pages 347-362) and index
Keywords: Philosophy; Theology